The effect of negative arousal on declarative memory - Constantinou, Marianna; Karadachka, Katherine; Marstaller, Lars; Burianová, Hana (Neuropsychologia, 2024)
Arousing events influence retrieval success, with a number of studies supporting a context-dependent effect of arousal on episodic memory retrieval. An improvement in speed and accuracy of episodic memories is observed when negative arousal is attached to them. In contrast, enhancing effects of negative arousal have not been reported to improve semantic memory retrieval. Episodic and semantic memory are highly interactive and yet differ based on their embedded contextual content. Although differences in brain activity exist between episodic and semantic memory, the two types of memory retrieval are part of a common long-term memory system. Considering the shared processes between episodic and semantic memory, the objectives of the current study were twofold: i) to examine, employing a novel paradigm, whether performance on episodic and semantic memory retrieval would be influenced differently by varying levels of arousal, between negative and neutral valence; and ii) to explore the neural patterns underlying these processes. Forty-seven healthy young adults were recruited and completed the experiment in the MRI scanner. The results demonstrated a negative arousal effect on the brain circuitry subserving both memory conditions as well as on behavioural performance, as indicated by better accuracy and faster reaction times. The study provides an insight into the role of negative arousal in memory processes and contributes to our understanding of the interplay between cognitive and emotional factors in memory modulation. Our work also highlights the highly interactive nature of episodic and semantic memory, and emphasises the importance in understanding how negative arousal interacts with the contextual content of a memory, on a behavioural and neurofunctional level.
Keywords: sémantika; Emotions; rozpomínání; lidé; Mental Recall; Brain Mapping; Episodic; Memory; Humans; fMRI; arousal; Memory, Episodic; epizodická paměť; mladý dospělý; Young Adult; mapování mozku; Context; mozek; Brain; emoce; Semantic; Arousal; Semantics